2022
DOI: 10.34172/ijbsm.2022.07
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phenolic and Flavonoid Contents, Antioxidant Properties, and Antimicrobial Activities of Stocksia Brahuica Benth

Abstract: Introduction: Stocksia brahuica Benth. (Sapindaceae) is an invaluable shrubby plant distributed in Iran, Afghanistan, and Balochistan region of Pakistan. In this study, the total phenolic and flavonoid contents and the antioxidant and antimicrobial properties of leaf, fruit, and seed extracts of S. brahuica were screened. Methods: Plant materials were collected in September 2021 from Zahedan, southeast of Iran. The total phenolic and flavonoid contents and total antioxidant capacity were assessed spectrophotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The GC/MS analysis study revealed that the tested extracts contained an abundant amount of components that can contribute to their effective antioxidant potential in DPPH assay. The chemical components identified that are classified in Table 2 confirm these statements, so that some of these components from classes such as labdane diterpenes, abietane di-terpenes, phenolic di-terpenes, oxygenated cembrene di-terpenes, oxygenated abietane di-terpenes, phenolic acids, resin acids, monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons, oxygenated sesquiterpenes, phenolic compounds, volatile phenolic compounds, tocopherols (Ebrahimnezhad et al 2022), lignans (Abdulkhani et al 2020), triterpenoids, and coumarins inhibited free radical scavenging activity in-vitro bioassay. The antioxidant activity of hydroethanolic extracts of branchlet of C. arizonica was higher than that of fruit, leaf, BHT, and AA, which can be caused by the amount of the some mentioned antioxidant components (Table 2).…”
Section: Antioxidant Activity (Aoa)mentioning
confidence: 69%
See 1 more Smart Citation
“…The GC/MS analysis study revealed that the tested extracts contained an abundant amount of components that can contribute to their effective antioxidant potential in DPPH assay. The chemical components identified that are classified in Table 2 confirm these statements, so that some of these components from classes such as labdane diterpenes, abietane di-terpenes, phenolic di-terpenes, oxygenated cembrene di-terpenes, oxygenated abietane di-terpenes, phenolic acids, resin acids, monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons, oxygenated sesquiterpenes, phenolic compounds, volatile phenolic compounds, tocopherols (Ebrahimnezhad et al 2022), lignans (Abdulkhani et al 2020), triterpenoids, and coumarins inhibited free radical scavenging activity in-vitro bioassay. The antioxidant activity of hydroethanolic extracts of branchlet of C. arizonica was higher than that of fruit, leaf, BHT, and AA, which can be caused by the amount of the some mentioned antioxidant components (Table 2).…”
Section: Antioxidant Activity (Aoa)mentioning
confidence: 69%
“…Phenolic compounds are widely found in plants and play an important role in antioxidant activity and scavenging free radicals through their hydroxyl groups (Cosme et al 2020;Ebrahimnezhad et al 2022), where deviates depending on their molecular structure and characteristics (Qian et al 2020;Falah et al 2021). In addition to phenolic compounds, other structures such as terpenes could develop antioxidant capacity in plant organs both solitarily or synergistically (Álvarez-Martínez et al 2021).…”
Section: Antioxidant Activity (Aoa)mentioning
confidence: 99%
“…2 filter paper, and the filtrate was dried using a rotary device (Heidolph, Germany) and a vacuum pump (distillation in a vacuum) and stored in the dark at 4°C until needed for experiments. The dried extract was then dissolved in dimethylsulfoxide (DMSO) (10%) to prepare a stock solution at a concentration of 200 mg/mL from each plant extract, from which desired concentrations were made (14). In the Agar well diffusion method, the extract concentration of 50 mg/mL was used.…”
Section: Preparation Of Plant Extracts and Salmonella Typhimurium Str...mentioning
confidence: 99%